Implementasi Pembinaan Kepribadian dan Keterampilan terhadap Narapidana pada Lembaga Pemasyarakatan Kelas II A Jambi - Herma Yanti; Maryati Maryati; Andika Yusriansyah (Universitas Batanghari Jambi, 2022)
Guidance of prisoners in Correctional Institutions is an important process in shaping personality as well as providing skills so that the stated coaching goals can be realized. For this reason, these coaching activities need to be carried out optimally according to the pattern of coaching as stipulated in the Decree of the Minister of Justice Number M.02-PK.04.10 of 1990, which includes personality development and skills development. Considering the large number of prisoners who are accommodated in the Jambi Class IIA Institute, this study aims to discuss how the implementation of personality development and skills development for these prisoners and other factors that also influence its implementation. Therefore, this study uses a socio legal research approach. To obtain field data, it was conducted through interviews with several correctional officers respondents who were considered relevant to the problem being studied. From the results of the study, it is known that the implementation of the guidance has not been optimally carried out. In addition to the main factor, the number of prisoners that far exceeds the capacity of the Correctional Institution so that it affects the availability of coaching facilities, it is also influenced by the staff's resource factor, and no less important is the quality of the resources involved in providing materials for some of the coaching activities carried out.